Characterisation of microcrystalline cellulose from oil palm fibres for food applications. (5th September 2016) - Xiang, Loo Yu; P. Mohammed, Mohd Afandi; Samsu Baharuddin, Azhari
Highlights: Microcrystalline cellulose was extracted from oil palm empty fruit bunches, stalk and spikelet. The microstructural, physicochemical and rheological properties of empty fruit bunches, stalk and spikelet throughout the chemical extraction processes were comparatively investigated and explained in this study. Stalk fibres are more preferable as a raw material for the production of MCC compared to EFB and spikelet fibres. Abstract: Microcrystalline cellulose (MCC) extracted from empty fruit bunches (EFB), stalk and spikelet were characterised through physicochemical and microstructure analyses. Raw stalk fibres yielded the highest cellulose content (42.43%), followed by EFB (32.33%) and spikelet (18.83%). Likewise, lowest lignin and residual oil content was reported in raw stalk fibres compared to EFB and spikelet. SEM revealed significant changes on fibres' surface morphology throughout the extraction process. FTIR analysis showed that main characteristic peaks of hemicellulose and lignin was absent on the extracted MCC. The crystallinity index for MCC extracted from EFB (82.5%), stalk (82.2%) and spikelet (86.5%) was comparable to commercial MCC (81.9%). Results suggested stalk fibres is more preferable for the production of MCC compared to EFB and spikelet. Further rheological studies showed viscoelastic behaviour with no significant differences between commercial and stalk-based MCC, while modelling work showed ability to simulate complex deformation of the MCC-hydrogel/food mixture during processing/handling stage.